A review of the right to basic education, the 2020 Covid-19 related schools' shutdown, and the courts in South Africa - Booi, Ntombizinhle Princess (University of the Witwatersrand, Johannesburg, 2024)
Owing to COVID-19, the South African government ordered the closure of educational facilities in the country to try and curtail the spread of the virus. At the time, no one knew the extent to which the virus had spread, its potency for the South African public, how it impacted on children and what actions the government could take, besides locking down the country. Both the government and the public were facing a pandemic of this kind for the first time. However, the closure of schools placed the educational rights of learners under a spotlight, as under the Constitution of the Republic of South Africa, 1996, basic education is a right. The closure of the schools had many consequences for the right to basic education, including that education delivery, as it was then known, had to be changed. Yet, it is reasonable to assume that many schools were ill equipped for the sudden change which could not have been foreseen. To this end, there had to be a way forward for schools, and online learning became a viable avenue for ensuring that education did not come to a standstill. Yet again, it is reasonable to assume that many schools would not have had the capacity to transition to, let alone facilitate and maintain, online learning. A preliminary conclusion then would be that COVID-19 had a direct impact on the right to education. This is only the start, however, because the next line of inquiry would be whether the decision of the state to close educational facilities through the lockdowns was reasonable, and consequently justified considering the limitation it brought to the right to education. This report concludes by examining two cases that addressed these questions.
A research report submitted in fulfillment of the requirements for the Master of Laws, In the Faculty of Faculty of Commerce, Law and Management, School of Law, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Education; 2020; COVID-19; shut down; SDG-4: Quality education